PENGEMBANGAN POSTER MEDIA TANAM JAMUR TIRAM DENGAN CAMPURAN LIMBAH BATANG PISANG PADA PEMBELAJARAN BIOLOGI KELAS X SMA - Roina Roina; Fitra Suzanti; Darmawati (Berugak Baca, 2025)
Osters are one of the image based learning media contain the lates innovations. This study aims to produce a poster design for oyster mushroom planting media with a mixture of banana stem waste in biology learning for clas x of high school. This study was conducted in februari – april 2025 at the naturallaboratory of biology education pmipa fkip, riau university. The design o this poster refers to the addie development model. At the analysis stag, an independent curiculum analysis was carried out on the biology material for calss x of high school issue by the ministry of education, culture, research and technology (kemendikbudristek). The analysis aims to determine atp and materials that the are suitable for use and made that are adjusted to learning objectives. The design stage is carried out by designing learning ecives and designing posters. The process of making poster media stars from compiling a framework with contents that the are made lengtwise with a4 paper size 29,5 x 21 cm. Based on the result of the analysis, design, and development, the result of the study can be used as one of the learning resources in the from of learning posters on the material on environmental chage and wase management for class x of high school, meeting 4.